Express-sovelluskehyksen soveltuvuus REST-ohjelmointirajapintojen toteuttamiseen - Kukkonen, Sami (2025)
The purpose of this study was to investigate the impact of the application framework on adherence to the REST architectural style and its characteristic best practices. Express was chosen as the application framework and the study was conducted as a case study. The study findings were formed from the observations during the practical implementation. The practical implementation consisted of creating an application programming interface that aimed to follow as precisely as possible the REST architectural style and some of the best practices around REST. According to the findings of this study, REST APIs can be implemented with Express but Express does not direct implementers to hardly any direction. For this reason, implementers using Express must completely understand what REST is and what the typical good practices of REST are.